Clinical significance of tumor‐infiltrating immune cells focusing on BTLA and Cbl‐b in patients with gallbladder cancer. Issue 12 (22nd October 2015) - Oguro, Seiji; Ino, Yoshinori; Shimada, Kazuaki; Hatanaka, Yutaka; Matsuno, Yoshihiro; Esaki, Minoru; Nara, Satoshi; Kishi, Yoji; Kosuge, Tomoo; Hiraoka, Nobuyoshi
Abstract : The host immune system plays a significant role in tumor control, although most cancers escape immune surveillance through a variety of mechanisms. The aim of the present study was to evaluate the clinicopathological significance of a novel co‐inhibitory receptor, B and T lymphocyte attenuator (BTLA), the anergy cell marker Casitas–B‐lineage lymphoma protein‐b (Cbl‐b), and clinical implications of tumor‐infiltrating immune cells in gallbladder cancer (GBC) tissues. We investigated 211 cases of GBC, 21 cases of chronic cholecystitis (CC), and 11 cases of xanthogranulomatous cholecystitis (XGC) using immunohistochemistry to detect tissue‐infiltrating immune cells and their expression of BTLA and Cbl‐b, and carried out correlation and survival analyses. The density of infiltrating T cells was significantly higher in CC and XGC than in GBC. The density ratio of BTLA + cells to CD8 + T cells (BTLA/CD8) and that of Cbl‐b + cells to CD8 + T cells (Cbl‐b/CD8) were significantly higher in GBC than in CC and XGC. The FOXP3/CD4, BTLA/CD8, and Cbl‐b/CD8 ratios were significantly correlated with each other, and also with malignant phenotypes. Survival analyses revealed that a lower density of tumor‐infiltrating CD8 + cells, and higher Foxp3/CD4, BTLA/CD8, and Cbl‐b/CD8 ratios were significantly associated with shorter overall survival and disease‐free survival in GBC patients. Multivariate analyses showed that M factor, perineural invasion, BTLA/CD8, and Cbl‐b/CD8 were closely associated with shorter overall survival. These findings suggest that higher ratios of BTLA/CD8 and Cbl‐b/CD8 are independent indicators of unfavorable outcome in GBC patients, and that upregulation of BTLA in cancer tissues is involved in inhibition of antitumor immunity. Abstract : Most of tumor‐infiltrating BTLA+ cells (black) are CD4+T cells (red) in gallbladder cancer.